Aperitifs, young people and minority languages - SILLANI, SANDRO; PASCOLINI, MAURO; ROMITO, FRANCESCA; NASSIVERA, FEDERICO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2020)
The aperitif is an expanding consumer good associated with modern lifestyles and sociality. This aim of the study was to evaluate whether the region of origin (Carnia) and the use of a minority language (Friulian) might serve as effective levers in the aperitif market. It was found that both the region of origin and the minority language can be effective, and that the language is an important reinforcement of the region of origin. In the case study considered - use of Friulian in the Friuli Venezia Giulia region - the minority language combined with a translation of the text into the majority language generated a competitive advantage, regardless of the consumers’ language skills and sense of regional belonging.